AFLATOXINS AND ITS EFFECT ON HUMAN AND ANIMALS: ARTICLE REVIEW - Athraa H.Mohsen; Israa H .Mohsen; Mohsen H.Risan (Scholar Express Journals, 2022)
Grains, fruits and various foodstuffs are contaminated with fungi and toxins resulting from improper storage before, after and during harvest. The degree of contamination depends on several factors including pH and moisture content, as well as the physical nature of the seeds as well as exposure to insects or microorganisms. Fungi are also characterized by the secretion of enzymes that affect much of the food content. They develop from carbohydrates, proteins and fats accompanied by increased oxidation or staining of food as a result of increased fatty acids that affect the color. The taste and flavor of food . Mycotoxins are a family of biological compounds produced by a group of fungi that have the ability to produce secondary metabolites (SM) when grown in an appropriate environment. The secondary metabolic products of fungi are biologically active compounds. In addition to being non-antigenic toxins, the components that prompt the living body to form antibodies, most of them are toxic.“In general, there is agreement that the secondary metabolic products of mycotoxins, as well as the resulting poisoning, should be called mycotoxins. In general, mycotoxins are generally referred to as human and animal food, and the contamination of food or food supplied by fungi, which is called contamination Direct, as food encourages the growth of fungi either during different production stages or during transportation or storage.
Keywords: Mycotoxins; secondary metabolites; fungi; contamination of food